Acquired myospherulosis secondary to gluteal augmentation on fine needle aspiration cytology: A diagnostic challenge. Issue 5 (14th December 2017) - Alperstein, Susan; Dilcher, Thomas; Viswanathan, Kartik; Rao, Rema A.; Siddiqui, Momin T.; Giorgadze, Tamara
Abstract : A 30‐year‐old female presented with a three‐month history of a multilocular cystic lesion over the lumbosacral spine. Fine‐needle aspiration biopsy (FNA) of the lesion was performed at an outside institution, and a cytologic diagnosis, suspicious for chordoma, was rendered. The patient presented for surgical consultation at our institution. Repeat FNA demonstrated an unusual fat‐like material. Upon further inquiry, the patient provided a recent history of gluteal contour improvement with fibroadipose tissue implants. A diagnosis of myospherulosis was made with a concurrent surgical pathology correlation. No evidence of chordoma was identified. To date, this is the first reported case of acquired myospherulosis in the context of gluteal contour enhancement and represents an important diagnostic pitfall to consider on cytology preparations.